Higher Body Mass Index Shows No Evidence of Association with Histopathologic Markers of Aggressiveness in Early-Stage Papillary Thyroid Carcinoma - Aliki Economides; Demetris Lamnisos; Paris Vogazianos; Konstantinos Giannakou; Savvas Frangos; Vasilis Constantinides; Panagiotis Papageorgis; Panayiotis A. Economides (Biomedicines, 2025)
Background: Obesity has been implicated in the pathogenesis and progression of several malignancies, including papillary thyroid carcinoma (PTC), but its role in tumor aggressiveness remains controversial. This study aimed to investigate the association between adiposity, as measured by body mass index (BMI), and histopathological features of aggressiveness in patients with PTC. Methods: This single-center retrospective study included 298 consecutive adult patients diagnosed with PTC between 2016 and 2021 at an endocrine referral center. Patients were stratified based on BMI into normal weight (<25 kg/m2) and overweight/obese (≥25 kg/m2) groups. Clinical, metabolic, and histopathological data were compared between the two groups. Results: Overweight/obese patients had significantly higher rates of hypertension, type 2 diabetes, fasting glucose, and triglycerides, as well as lower high-density lipoprotein cholesterol (all p < 0.01). Tumor size was similar between groups, with over 85% of tumors measuring ≤ 1 cm (microcarcinomas) and no significant difference in the proportion of tumors > 1 cm (p = 0.582). There were no significant differences in multifocality (p = 0.269) or extrathyroidal extension (ETE) (p = 0.826). Lymph node metastases occurred in 34% of normal weight and 28% of overweight/obese patients, without a statistically significant difference (p = 0.402). Lymph node compartment involvement did not significantly differ between groups (p = 0.160). Conclusions: Despite being associated with adverse metabolic profiles, higher BMI was not linked to tumor aggressiveness in patients with predominantly early-stage PTC. As the incidence of obesity and PTC continues to rise, these findings highlight the need for further research into early-stage PTC biology and more precise risk measures of adiposity beyond BMI alone.